Involvement of dopamine loss in extrastriatal basal ganglia nuclei in the pathophysiology of Parkinson’s disease - Benazzouz, Abdelhamid; Mamad, Omar; Abedi, Pamphyle; Bouali-Benazzouz, Rabia; Chetrit, Jonathan (Frontiers in Aging Neuroscience, 2014)
Parkinson’s disease is a neurological disorder characterized by the manifestation of motor symptoms, such as akinesia, muscle rigidity and tremor at rest. These symptoms are classically attributed to the degeneration of dopamine neurons in the pars compacta of substantia nigra (SNc), which results in a marked dopamine depletion in the striatum. It is well established that dopamine neurons in the SNc innervate not only the striatum, which is the main target, but also other basal ganglia nuclei including the two segments of globus pallidus and the subthalamic nucleus. The role of dopamine and its depletion in the striatum is well known, however, the role of dopamine depletion in the pallidal complex and the subthalamic nucleus in the genesis of their abnormal neuronal activity and in parkinsonian motor deficits is still not clearly determined. Based on recent experimental data from animal models of Parkinson's disease in rodents and non-human primates and also from parkinsonian patients, this review summarizes current knowledge on the role of dopamine in the modulation of basal ganglia neuronal activity and also the role of dopamine depletion in these nuclei in the pathophysiology of Parkinson's disease.